Endothelial Dysfunction during Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis. (4th March 2021) - Theodorakopoulou, Marieta P.; Bakaloudi, Dimitra Rafailia; Alexandrou, Maria Eleni; Papakosta, Despoina; Pataka, Athanasia; Kioumis, Ioannis; Boutou, Afroditi K.
Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by high cardiovascular risk, which is further amplified during acute COPD exacerbations (AECOPD). Endothelial dysfunction has been previously suggested as one of the potential pathogenetic mechanisms. In order to study the effects of AECOPD on endothelial function assessed by available functional methods, we performed a literature search involving Pubmed and Scopus databases. Eligible studies were those that included adult patients with COPD and evaluated endothelial damage via semi-invasive or noninvasive functional methods, during AECOPD and after recovery or in stable condition. Newcastle-Ottawa Scale was applied to evaluate the quality of retrieved studies. Endothelial function was significantly impaired during AECOPD compared to recovery/stable condition (SMD: −0.87, 95%CI [−1.19, −0.55]). Patients during AECOPD presented a significantly worse response in endothelium-dependent (flow-mediated dilatation WMD: −2.59, 95%CI [−3.75, −1.42]) and independent vasodilation (nitroglycerine-mediated dilatation WMD: −3.13, 95%CI [−5.18, −1.09]) compared to recovery. Sensitivity analyses confirmed the above results. In conclusion, endothelium-dependent and independent vasodilation is worse during AECOPD compared to the stable condition. Endothelial dysfunction could play a role in the high cardiovascular risk during AECOPD.